HIV and Malaria - Parwitasari, Ririek; Nasronudin, Nasronudin (Institute of Topical Disease, 2014)
HIV/AIDS is a global problem involving industrialized and developing country including Indonesia. Malaria has killed millions of human beings almost 3 million people each year, whereas since 1999, nearly 36 million people in the world infected with HIV and 3 million more have died (Kakilaya, 2006). HIV infection increases the risk and aggravate malaria. In Africa in the area of malaria transmission intensities high and low, HIV aggravate malaria and improve case fatality at any age (Eline 2006). HIV is an RNA viruses whose hallmark is the reverse transcriptation of its genomic. Malaria is a protozoan disease transmitted by the bite of infected anopheles mosquito. Infection malaria can stimulate HIV replication and may cause faster progression of HIV disease.